(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article covers the field of pragmalinguistics and the history of its analytical formation. The article discusses the main concepts, approaches and modern research directions in the field of pragmalinguistics. The use of language in social, cultural, and technological contexts will be covered, as well as